Using the IUCN Green List of Protected and Conserved Areas to promote conservation impact through marine protected areas. (September 2016) - Wells, Sue; Addison, Prue F.E.; Bueno, Paula A.; Costantini, Marco; Fontaine, Anne; Germain, Laurent; Lefebvre, Thierry; Morgan, Lance; Staub, Francis; Wang, Bin; White, Alan; Zorrilla, María X.
Abstract: With the number of marine protected areas (MPAs) growing rapidly and progress being made towards protecting 10% of the ocean, as called for by the Convention on Biological Diversity, there is equally a need to increase efforts and provide incentives for effective management of these sites. The IUCN Green List of Protected and Conserved Areas (GLPCA), a voluntary global standard that protected areas and their agencies may decide to commit to working towards, has been set up to contribute to this. Protected areas can achieve Green List status by demonstrating a certain performance level and by meeting outcomes measured against a set of defined criteria. An assured verification process is followed before sites are recognized. The GLPCA will thus encourage and identify those protected areas (both terrestrial and marine) that are effectively managed, have equitable governance and achieve significant conservation impacts. The GLPCA pilot phase announced the first 25 protected areas to meet the criteria at the IUCN World Parks Congress in Sydney in November 2014. These included four MPAs: Iroise Natural Marine Park, Cerbère‐Banyuls Natural Nature Reserve, and Guadeloupe National Park in France, and Gorgona National Park in Colombia. Italy and China also participated in the pilot phase and each has an MPA that is continuing to work towards GLPCA status. The experiences of these sites are described, as well as three other programmes (two regional and one global) that are being developed to promote improved management of MPAs. This information will be useful for other MPAs considering participation in the GLPCA initiative. Copyright © 2016 John Wiley & Sons, Ltd.